Dissection of Functional Modules of AT-HOOK MOTIF NUCLEAR LOCALIZED PROTEIN 4 in the Development of the Root Xylem - Seo, Minji; Lee, Ji-Young (Frontiers in Plant Science, 2021)
Xylem development in the Arabidopsis root apical meristem requires a complex cross talk between plant hormone signaling and transcriptional factors (TFs). The key processes involve fine-tuning between neighboring cells, mediated via the intercellular movement of signaling molecules. As an example, we previously reported that AT-HOOK MOTIF NUCLEAR LOCALIZED PROTEIN (AHL) 4 (AHL4), a member of the 29 AT-hook family TFs in Arabidopsis, moves into xylem precursors from their neighbors to determine xylem differentiation. As part of the effort to understand the molecular functions of AHL4, we performed domain swapping analyses using AHL1 as a counterpart, finding that AHL4 has three functionally distinctive protein modules. The plant and prokaryotes conserved (PPC) domain of AHL4 acts as a mediator of protein–protein interactions with AHL members. The N-terminus of AHL4 is required for the regulation of xylem development likely via its unique DNA-binding activity. The C-terminus of AHL4 confers intercellular mobility. Our characterization of modules in the AHL4 protein will augment our understanding of the complexity of regulation and the evolution of intercellular mobility in AHL4 and its relatives.